(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Spinal tuberculosis (TB) accounts for 1–2% of all cases of TB and is a common extrapulmonary form. The duration of the rehabilitation period in patients operated on in the IV stage of the tuberculosis process complicated by abscessing is twice as long as the duration of treatment of patients operated on in the I-II stages of spinal tuberculosis. The number of purulent-inflammatory complications in the early postoperative period in patients with spinal tuberculosis in stages III-IV with abscess reaches 22.2%. Although it is primarily a skeletal disease, secondary involvement of the nervous system may lead to diverse neurological disabilities.